Molecular Considerations and Evolving Surgical Management Issues in the Treatment of Patients with a Brain Tumor - Lichtor, Terry (IntechOpen, 2015)
A dramatic increase in knowledge regarding the molecular biology of brain tumors has been established over the past few years. In particular, recent new avenues regarding the role of microRNAs along with further understanding of the importance of angiogenesis, immunotherapy and explanations for the resistance of the tumors to radiation therapy have been developed. A discussion of certain surgical management issues including improvements in imaging along with issues concerning tumor induced epilepsy is included. It is hopeful that this new information will lead to efficacious treatment strategies for these tumors which remain a challenge. In this book, a review of the latest information on these topics along with a variety of new therapeutic treatment strategies with an emphasis on molecular targeted therapies is provided.